The Decision of Choosing Course in the Era of Covid 19 through the Telemarketing Program, Personal Selling and College Image - Ester Hervina Sihombing; Nasib Nasib (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The main focus in this study is to analyze the influence of variable telemarketing, personal selling and the image of universities. This research was conducted at a high school in Medan. Data collection using questionnaires with the technique of withdrawing samples as many as 237 respondents through withdrawal by way of snowball sampling. The results showed that telemarketing had a positive effect on college decisions. Personal selling has a positive effect on the decision to choose a lecture. The image of the college has a positive and significant positive effect on the decision to choose a college.